Ngao : An Exclamation to Enhance the Role of the Digital Age - Kemkan, Wilaiwan (Academic MCU Buriram Journal, 2024)
The purposes of this research were: 1) to study the origin of the word " Ngaw " and in what contexts it is used, 2) to study how to create slang today; The method of conducting the study was to study the use of slang by collecting information from online media Twitter and Facebook, from sentences used in 2017, and then collecting sentences in which the word "Ngaw" appeared that it is used in what manner; Including a study of how to create slang by the researcher, synthesizing research, and articles that study slang, and then summarizing and discussing the results. The research result found that: 1. The origin of the word " Ngaw " found that context in which the word "Ngaw" is used is 1) in messages used to joke among men and women, 2) showing a slight feeling of disappointment, 3. shows the need for sarcasm; The word "Ngaw" is a short exclamation used among Thai teenagers. (2017), commonly used to convey meaning in expressing liking for something, or to express feelings to emphasize a situation, or an event being discussed; with the meaning of understanding language, with just Context-he events being discussed at that time. and that group of speakers; and the results of the study of methods for creating slang from synthesis. 2. It was found that there are methods of creating structural slang from word combinations and the process of creating slang from other special characteristics.